2023
DOI: 10.1186/s12863-023-01180-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between human blood metabolome and the risk of hypertension

Nannan Dai,
Yujuan Deng,
Baishi Wang

Abstract: Hypertension, commonly referred to as high blood pressure, is a chronic medical condition characterized by persistently elevated blood pressure levels. It is a prevalent global health issue, affecting a significant portion of the population worldwide. Hypertension is often asymptomatic, making it a silent but potentially dangerous condition if left untreated. Genetic instruments for 1,091 were from a recent comprehensive metabolome genome-wide association study (GWAS). Summary statistics of diastolic blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, no metabolites significantly correlated with SBP. In the MR analysis by Dai et al ( 62 ), 12 metabolites were significantly associated with DBP and 22 metabolites with SBP. Sensitivity analysis revealed that four metabolites, namely 1-(1-enyl-stearoyl)-2-arachidonoyl-GPE (P-18:0/20:4)* (OR = 0.79, 95% CI: 0.70–0.88, P = 3.78 −05 ), behenoyl dihydrosphingomyelin [d18:0/22:0]* (OR = 1.84, 95% CI: 1.39–2.44, P = 2.04 −05 ), N-acetylarginine (OR = 1.15, 95% CI: 1.08–1.22, P = 1.17 −05 ), and N-acetylglutamine (OR = 1.15, 95% CI: 1.08–1.22, P = 1.17E −05 ), were significantly associated with DBP, and one metabolite, namely X-11381 (OR = 1.58, 95% CI: 1.28–1.94, P = 1.58 −05 ), was examined for its significant association with SBP.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, no metabolites significantly correlated with SBP. In the MR analysis by Dai et al ( 62 ), 12 metabolites were significantly associated with DBP and 22 metabolites with SBP. Sensitivity analysis revealed that four metabolites, namely 1-(1-enyl-stearoyl)-2-arachidonoyl-GPE (P-18:0/20:4)* (OR = 0.79, 95% CI: 0.70–0.88, P = 3.78 −05 ), behenoyl dihydrosphingomyelin [d18:0/22:0]* (OR = 1.84, 95% CI: 1.39–2.44, P = 2.04 −05 ), N-acetylarginine (OR = 1.15, 95% CI: 1.08–1.22, P = 1.17 −05 ), and N-acetylglutamine (OR = 1.15, 95% CI: 1.08–1.22, P = 1.17E −05 ), were significantly associated with DBP, and one metabolite, namely X-11381 (OR = 1.58, 95% CI: 1.28–1.94, P = 1.58 −05 ), was examined for its significant association with SBP.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, Qiao et al ( 61 ) and Dai et al ( 62 ) conducted MR analyses on blood metabolites and blood pressure, focusing on systolic blood pressure (SBP) and diastolic blood pressure (DBP). However, this study targets EHT, indicating a difference in study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, no metabolites significantly correlated with SBP. In the MR analysis by Dai et al (62), 12 metabolites were significantly associated with DBP and 22 metabolites with SBP. Sensitivity analysis revealed that four metabolites, namely 1-(1-enyl-stearoyl)-2arachidonoyl-GPE (P-18:0/20:4)* (OR = 0.79, 95% CI: 0.70-0.88, P = 3.78 −05 ), behenoyl dihydrosphingomyelin [d18:0/22:0]* (OR = 1.84, 95% CI: 1.39-2.44, P = 2.04 −05 ), N-acetylarginine (OR = 1.15, 95% CI: 1.08-1.22, P = 1.17 −05 ), and N-acetylglutamine (OR = 1.15, 95% CI: 1.08-1.22, P = 1.17E −05 ), were significantly associated with DBP, and one metabolite, namely X-11381 (OR = 1.58, 95% CI: 1.28-1.94, P = 1.58 −05 ), was examined for its significant association with SBP.…”
Section: Discussionmentioning
confidence: 95%